A singular mediação entre cultura e economia: economia criativa como estratégia de desenvolvimento - Barbara Freitas Paglioto (2015)
The aim is to search up arguments for the understanding of the meanings of the term creative economy considering its historical origins - which dates back to the sphere of public policies - within the so-called Information Society. More specifically, we intend to understand what it means to consider creative economy as a development strategy for peripheral countries, since the concept already carries a number of meanings that may prove incompatible with a development project thought from the periphery point of view. The year of 2014 marks a decade of the beginning of the debate on the subject in Brazil, which was inserted under the strong influence of multilateral organizations and foreign models from countries like Australia and the UK. However, even today, what we see is that the views on the meanings, the potential and the demands generated around the construction of public and private projects built around the notions of the creative economy, are quite disparate. The idea of creative economy embodies both the relation between arts, cultural industries and technological renewal from which it derives its emphasis on intellectual property and on production of functional goods (in fashion, advertising, architecture, etc.) as cultural and economic urban questions through the concepts of creative class, creative clusters and creative city. Its definition and practice are born as a way to guide the relationship between culture and economy in a particular direction, shaping the culture to serve as an economic valuation tool or as a resource for development. When implemented in the context of peripheral economies, the categories of the creative economy are influenced by their socioeconomic, cultural and political characteristics, as well as by the struggles and interests surrounding them, from which they have to be rethought. This new perspective raises questions concerning, for example, the potential of the creative economy for reducing inequalities and for citizen empowerment; its connection with informal sectors, with traditional cultures, etc.